Розрахункова оцінка середньоексплуатаційної паливної економічностї двигуна легкового автомобіля - Осетров, Олександр Олександрович; Альохін, Дмитро Сергійович; Бекарюк, Олександр Миколайович (НТУ "ХПІ", 2018)
Запропоновано комплексну математичну модель робочого процесу двигуна внутрішнього згоряння у складі автомобіля. З використанням цієї моделі визначено поточні і середні експлуатаційні показники двигуна при русі автомобіля на режимах випробувального циклу NEDC. Проаналізовано вплив радіуса коліс, висоти та маси транспортного засобу, моменту запалювання, ефективності трансмісії та опору дорожньої поверхні на середню експлуатаційну витрату палива. Також розглянуто перспективи подальших досліджень.

The objective of the paper is estimation of the average operational fuel economy of a car engine. The efficiency of the car engine working process depends on its design parameters, the intensity of the gear shift, driving style, driving mode. In order to estimate the influence of various factors on the average fuel-economic and environmental performance of the engine, various test cycles are used. In European countries the NEDC test cycle is considered as a basic one. In the paper a complex mathematical model of the working process of the vehicle engine is presented. Using the mathematical model the parameters of the engine are determined for the car moving in the modes of the NEDC test cycle. As a result of processing the data at all points of the cycle the average operating parameters of the engine are obtained. The influence of the wheel radius, height and mass of the vehicle, ignition timing, transmission efficiency and resistance of the road surface on the engine average operating fuel consumption is analyzed. We also consider some recommendations for further research.
Calculated estimate of the average operating fuel economy of a car engine
Keywords: математичне моделювання; робочий процес; випробувальний цикл; середня витрата палива; NEDC; mathematical modeling; working process; test cycle